Concept of a Perfect Man: A Religious Perspective - Nangraj, Abdul Latif (Al Khadim Research Journal of Islamic Culture and Civilization, 2023)
Man is a complicated being because its nature is a combination of angelic character and satanic character, its nature has been an interesting area for debate among philosophers, educationists and psychologist. In order to create a peaceful society and to bring tranquility among human beings, it is necessary to analyze complicatedness of this nature. This paper is aiming to shadow light on this complicatedness and provide basic principles which can play vital role to create perfect and balanced personality. Main objective of this study is providing the suggestions to global organizations and states for restoring the peace and prosperity into the societies by pointing out the negative elements which are postulated in the nature from environment and advising the path which leads to create humanistic society, it is only possible when we are clear about the concept of perfect man, So this paper is regarded to give picture of perfect man in the perspective of religious study. https://doi.org/10.5281/zenodo.10519586